2021
DOI: 10.1002/alz.12327
|View full text |Cite
|
Sign up to set email alerts
|

Associations of loneliness with risk of Alzheimer's disease dementia in the Framingham Heart Study

Abstract: Introduction:The relationship between persistent loneliness and Alzheimer's disease (AD) is unclear. We examined the relationship between different types of mid-life loneliness and the development of dementia and AD.Methods: Loneliness was assessed in cognitively normal adults using one item from the Center for Epidemiologic Studies Depression Scale. We defined loneliness as no loneliness, transient loneliness, incident loneliness,or persistent loneliness, and applied Cox regression models and Kaplan-Meier plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 37 publications
6
57
1
Order By: Relevance
“…Change in loneliness did not correlate with dementia risk, which is consistent with two recent findings (Akhter-Khan et al, 2021;Lee et al, 2021). In the Framingham Heart Study, for example, only those who reported persistent (i.e., constant) loneliness had increased risk of dementia; participants whose loneliness scores changed across the two waves had decreased or equivalent dementia risk compared to those who reported not feeling lonely at either wave (Akhter-Khan et al, 2021). The average population trajectory in the current study suggests that loneliness is expected to change, with most experiencing worsening levels of loneliness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Change in loneliness did not correlate with dementia risk, which is consistent with two recent findings (Akhter-Khan et al, 2021;Lee et al, 2021). In the Framingham Heart Study, for example, only those who reported persistent (i.e., constant) loneliness had increased risk of dementia; participants whose loneliness scores changed across the two waves had decreased or equivalent dementia risk compared to those who reported not feeling lonely at either wave (Akhter-Khan et al, 2021). The average population trajectory in the current study suggests that loneliness is expected to change, with most experiencing worsening levels of loneliness.…”
Section: Discussionsupporting
confidence: 92%
“…We replicated prior findings by showing that mild levels of baseline loneliness predict a 43% increased risk of dementia. Consistent with newly reported findings (Akhter-Khan et al, 2021), change in loneliness did not correlate significantly with dementia risk. Future research should investigate whether chronicity of loneliness is a key feature that increases risk of dementia.…”
Section: Discussionsupporting
confidence: 90%
“…54 The temporal dynamics of social isolation may link to different neural activity and health consequences. Akhter-Khan et al 55 reported that transient loneliness was resilient to dementia risk. Consequently, future research should consider the trajectory of social isolation and loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…54 The temporal dynamics of social isolation may link to different neural activity and health consequences. Akhter-Khan et al 55…”
Section: Discussionmentioning
confidence: 99%
“…Although longitudinal studies cannot establish causal directionality, these studies consistently demonstrate an association between loneliness and subsequent cognitive decline [ 63 ]. Loneliness has reliably been associated with increased risk of Alzheimer’s disease and related dementias [ 66 , 67 , 68 , 69 ], in addition to worse behavioral and psychological symptoms of dementia [ 70 ]. Moreover, this increase in dementia risk seems to be most relevant for individuals with persistent loneliness compared to individuals with transient loneliness in whom dementia risk remains unchanged [ 67 ].…”
Section: Discussionmentioning
confidence: 99%